Advanced gas separation via combined use of carbon nanomaterials and microporous materials - Li, Wen (2019)
Extensive research on gas adsorption and separation has been widely developed in view of the requirement of effective CO2 and H2 capture as well as biogas upgrading (CO2/CH4 separation) so as to ensure a sustainable environment for future generation. Thus, with regards to this behavior, microporous materials and carbon nanomaterials are potential candidates to be developed and utilized as adsorbents and membranes, due to their excellent capabilities for effective gas separation, lower capital cost and energy penalty, together with feasibility of scale-up into industrial operations. Herein, the objectives of this thesis are: (1) Tailoring gas uptake capacities for a three-dimensional nanocomposite that leads to an increase of overall gas adsorption sites; (2) Optimizing mixed-matrix membranes (MMMs) with the combined use of carbon nanomaterials and microporous materials to achieve improved gas separation performance; (3) Developing carbon molecular sieve membranes (CMSMs) with functionalized microporous materials to fulfill excellent gas permeation.